Outdoor Learning-Based Mathematics Learning: Characteristics, Challenges, and Implications for PMRI Math Trail Design - Mardia, Ainun; zulkardi, zulkardi; Putri, Ratu Ilma Indra; Kamid, Kamid (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
The research investigates methods to enhance student learning experiences through authentic and relevant educational activities in modern mathematics classrooms. Outdoor learning serves as an educational approach that enables students to develop better physical and mental involvement in their learning activities. The Indonesian educational system faces multiple systemic barriers that prevent outdoor learning from becoming a standard practice in schools. Research to date focuses on the teaching methods that teachers use during math trail activities, but it does not fully connect these practices to the principles of Indonesian Realistic Mathematics Education (PMRI). The research investigates outdoor mathematics learning characteristics while identifying implementation obstacles and evaluating their effects on PMRI-based math trail development. The research design uses descriptive qualitative methods, which combine data from three sources through observation, interviews, and document analysis for triangulation purposes. The research shows that outdoor mathematics education contains real-world characteristics and participatory and exploratory elements and contextual grounding but fails to follow essential PMRI standards. The research provides practical recommendations that help developers create learning paths that adapt to specific learning environments. The research applies PMRI theory to outdoor learning environments, which creates new possibilities for using contextual learning to teach mathematics through environmental exploration in Indonesian schools.